A four-element UWB MIMO antenna using SRRs for application in satellite communications - Chafai Abdelhamid; Hedi Sakli; Nizar Sakli (International Journal of Electrical and Computer Engineering (IJECE), 2021)
This paper proposes a method for designing a new ultra wide band (UWB) multiple-input multiple-output (MIMO) antenna with two and four elements. First we presented an ultra-wide band antenna we studied these performances. Then, we studied the application of metamaterials to the design of MIMO antennas for miniaturization and the performance of antennas, in order to guarantee the proper functioning of the MIMO system with a much reduced separation distance between the radiating elements (λ/12), where the coupling can be very weak. The application of these circular double ring SRRs materials on the front plan of the antenna has contributed to the increasing of the antenna performance is studied in terms of S-Parameters, efficiency, diversity gain (DG), radiation properties and envelop correlation coefficient (ECC). It offers advantages such as the reduction of weight and congestion that is beneficial for their integration into satellite communications systems.